The Role of CdS:O/CdS Bilayer in the Formation of CdS1-xTex Intermixed Layer in CdTe Absorber - Das N.K.; Farhad S.F.U.; Rahman K.S.; Matin M.A.; Amin N. (Institute of Electrical and Electronics Engineers Inc., 2023)
Cadmium sulfide; Cadmium telluride; Conversion efficiency; II-VI semiconductors; Morphology; Near infrared spectroscopy; Semiconductor alloys; Thin film solar cells; Thin films; X ray diffraction; CdTe cells; Close spaced sublimation; Columnar growth; Power conversion efficiencies; SEM image; Solar cell performance; Source temperature; UV-vis-NIR spectroscopy; Cadmium alloys